Apostasy: consequences on marriage and the custody of the child / Syahrul Syazwan Salehin, Mohd Salehuddin Mohd Salleh and Sareena Yanti Hassan Sabri. - Salehin, Syahrul Syazwan; Mohd Salleh, Mohd Salehuddin; Hassan Sabri, Sareena Yanti (Faculty of Law, 2007)
This research is conducted for the purpose of reviewing the current law on the effect of apostasy upon marriage and the custody of the child. Besides that, it is conducted to provide a better understanding and awareness regarding these issues in Malaysia. This would be conducted through library research that includes primary and secondary sources as well as interview. The importance of the study is to provide useful legal data and information.